Susceptibility of Mycobacterium tuberculosis-infected host cells to phospho-MLKL driven necroptosis is dependent on cell type and presence of TNFα. Issue 8 (17th November 2017) - Butler, Rachel E.; Krishnan, Nitya; Garcia-Jimenez, Waldo; Francis, Robert; Martyn, Abbe; Mendum, Tom; Felemban, Shaza; Locker, Nicolas; Salguero, Francisco J.; Robertson, Brian; Stewart, Graham R.
ABSTRACT: An important feature of Mycobacterium tuberculosis pathogenesis is the ability to control cell death in infected host cells, including inhibition of apoptosis and stimulation of necrosis. Recently an alternative form of programmed cell death, necroptosis, has been described where necrotic cell death is induced by apoptotic stimuli under conditions where apoptotic execution is inhibited. We show for the first time that M. tuberculosis and TNFα synergise to induce necroptosis in murine fibroblasts via RIPK1-dependent mechanisms and characterized by phosphorylation of Ser345 of the MLKL necroptosis death effector. However, in murine macrophages M. tuberculosis and TNFα induce non-necroptotic cell death that is RIPK1-dependent but independent of MLKL phosphorylation. Instead, M. tuberculosis -infected macrophages undergo RIPK3-dependent cell death which occurs both in the presence and absence of TNFα and involves the production of mitochondrial ROS. Immunocytochemical staining for MLKL phosphorylation further demonstrated the occurrence of necroptosis in vivo in murine M. tuberculosis granulomas. Phosphorylated-MLKL immunoreactivity was observed associated with the cytoplasm and nucleus of fusiform cells in M. tuberculosis lesions but not in proximal macrophages. Thus whereas pMLKL-driven necroptosis does not appear to be a feature of M. tuberculosis -infected macrophage cell death, it may contribute to TNFα-induced cytotoxicity of the lung stroma and therefore contribute to necrotic cavitation and bacterial dissemination.